2021
DOI: 10.1037/rev0000281
|View full text |Cite
|
Sign up to set email alerts
|

A counterfactual simulation model of causal judgments for physical events.

Abstract: How do people make causal judgments about physical events? We introduce the counterfactual simulation model (CSM) which predicts causal judgments in physical settings by comparing what actually happened with what would have happened in relevant counterfactual situations. The CSM postulates different aspects of causation that capture the extent to which a cause made a difference to whether and how the outcome occurred, and whether the cause was sufficient and robust. We test the CSM in several experiments in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 222 publications
(415 reference statements)
0
120
1
Order By: Relevance
“…Gerstenberg and colleagues (2021) have reported similar results in the domain of intuitive physics. They were able to model the causal judgments that humans make about simple physical events by assuming that participants use a predictive physics engine to simulate counterfactuals.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Gerstenberg and colleagues (2021) have reported similar results in the domain of intuitive physics. They were able to model the causal judgments that humans make about simple physical events by assuming that participants use a predictive physics engine to simulate counterfactuals.…”
Section: Discussionmentioning
confidence: 60%
“…We found that many existing formal models of causal judgment could not make clear quantitative predictions about the current election case (see Supplementary Information https://osf.io/6jgez/). For example, some are only designed to account for intuitions about physical events (e.g., Wolff, 2007; Gerstenberg et al., 2021), whereas others are only designed for scenarios with a simpler causal structure (e.g., Morris et al., 2018). We were able to derive clear predictions for two other models of causal judgment.…”
Section: Methodsmentioning
confidence: 99%
“…Much of this type of thinking can be understood as deriving from people's intuitive theories-explanatory frameworks, analogous to scientific theories, that capture the causal and logical structure of the world within a domain. From early in life, people are driven to seek out such causal explanations and to use their mental representations of these causal systems to explain, predict, and intervene in the world (see Carey, 2009;Gelman & Legare, 2011;Gerstenberg et al, 2021;Gopnik & Wellman, 1994;Keil, 1994;Murphy & Medin, 1985; H. M. Wellman & Gelman, 1992 for influential treatments of this topic).…”
Section: Modeling and Leveraging Intuitive Theories To Improve Vaccin...mentioning
confidence: 99%
“…One of the most prominent ways to explain causal judgments is by employing counterfactual theories, on which causal judgments depend on counterfactual thinking (Gerstenberg et al, 2017(Gerstenberg et al, , 2021Hitchcock, 2007;Lewis, 1974;Paul, 2010). On such views, when someone wants to know if an event caused an outcome, they imagine a counterfactual alternative where the event did not happen and ask if the outcome still would have happened in that alternative scenario.…”
Section: Introductionmentioning
confidence: 99%
“…While counterfactual theories explain a wide array of causal judgments (Gerstenberg et al, 2021), cases of double prevention are a major challenge for our best theories of causal judgment (Bernstein, 2017;Hall, 2000Hall, , 2004Hitchcock, 2010;Paul, 2010;Woodward, 2012); counterfactual theories fail to explain why people tend accept the productive factor and reject the double preventer as the cause of the outcome in double-prevention scenarios. When someone imagines the counterfactual where Mike had not knocked into the bottle, the beer would not have spilled in this alternative scenario-ceteris paribus.…”
Section: Introductionmentioning
confidence: 99%